The legality of outright monetary transactions (OMT) of the European system of central banks - Helmut Siekmann (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2015)
In its meeting on 6 September 2012, the Governing Council of the ECB took decisions on a number of technical features regarding the Eurosystem's outright transactions in secondary sovereign bond markets (OMT). This decision was challenged in the German Federal Constitutional Court (GFCC) by a number of constitutional complaints and other petitions. In its seminal judgment of 14 January 2014, the German court expressed serious doubts on the compatibility of the ECB's decision with the European Union law. It admitted the complaints and petitions even though actual purchases had not been executed and the control of acts of an organ of the EU in principle is not the task of the GFCC. As justification for this procedure the court resorted to its judicature on a reserved "ultra vires" control and the defense of the "constitutional identiy" of Germany. In the end, however, the court referred the case pursuant to Article 267 TFEU to the European Court of Justice (ECJ) for preliminary rulings on several questions of EU law. In substance, the German court assessed OMT as an act of economic policy which is not covered by the competences of the ECB. Furthermore, it judged OMT as a - by EU primary law - prohibited monetary financing of sovereign debt. The defense of the ECB (disruption of monetary policy transmission mechanism) was dismissed without closer scrutiny as being "irrelevant". Finally the court opened, however, a way for a compromise by an interpretation of OMT in conformity with EU law under preconditions, specified in detail. Procedure and findings of this judgment were harshly criticized by many economists but also by the majority of legal scholars. This criticism is largely convincing in view of the admissibility of the complaints. Even if the "ultra vires" control is in conformity with prior decisions of court it is in this judgment expanded further without compelling reasons. It is also questionable whether the standing of the complaining parties had to be accepted and whether the referral to the ECJ was indicated. The arguments of the court are, however, conclusive in respect of the transgression of competences by the ECB and - to somewhat lesser extent - in respect of the monetary debt financing. The dismissal of the defense as "irrelevant" is absolutey persuasive.
urn:nbn:de:hebis:30:3-374824
Keywords: 330